Regulatory T cells in the induction and maintenance of peripheral transplantation tolerance. - Cobbold, S; Graca, L; Lin, C; Adams, E; Waldmann, H (2003)
It is now possible to induce donor-specific transplantation tolerance in adult rodents using non-depleting monoclonal antibodies against T cell co-receptor and co-stimulation molecules or by immunisation with tolerogenic antigen-presenting cells. It is a common finding of all these models of peripheral tolerance, as well as of various mouse models of autoimmune disease, that regulatory CD4(+) T cells are the principal mediators. There are currently no specific markers for regulatory T cells, but in some autoimmune models their activity has been associated with the expression of activation markers such as CD25 and CTLA4, or anti-inflammatory cytokines such as IL-10 and TGF-beta. CD4(+)CD25(+) T cells from both naïve and tolerised donors are able to transfer tolerance to grafts in lymphopenic recipients, and this may be directly applicable to bone-marrow transplantation. The challenge is now to understand the biological principles that allow such immune re-programming so that they can be safely applied to clinical organ grafting.